Assessment of quality of life in covid-19 patients post recovery- an observational analytical study - G, Sai Padmini; P, Sumathya; M, Ratna Jyothirmai; B, Niharika; S, Gunasekhar; B, Tejasree (Journal of Innovations in Applied Pharmaceutical Science (JIAPS), 2022)
The novel coronavirus has become rapidly widespread, resulting in an epidemic throughout China followed by a pandemic, an increasing number of cases in various countries throughout the world. During the Post COVID-19 period, the quality of life of several people has been impacted to varying extents. The physical health of the patients has shown a significant decline after getting recovered from COVID-19. We have done a community survey and have assessed the physical health of 400 subjects and have observed that there is a limitation in the physical activities of the subjects.